Maintenance management of public building: Ministry of Transport / Husnil Khatimah Abdul Rahman - Abdul Rahman, Husnil Khatimah (Faculty of Architecture, Planning and Surveying, 2008)
Maintenance management is very important to apply in each building. This is to ensure the building well function and efficient. All buildings need maintenance to retain the condition of the building. Maintenance management that consists of maintenance program, maintenance policy, and maintenance standard and so on should be adapted to the building. By providing this maintenance management to the building it will give a lot of benefit and advantage to the user and the public. It is to ensure the building getting worse in the future.